Sociocultural Considerations and the Challenges of Literary Translation: The Case of L’Aventure Ambiguë Into The Ambiguous Adventure - Ladan, Saliha (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
Abstract L’Aventure ambiguë written by Cheikh Hamidou Kane was translated into English titled The Ambiguous Adventure by Katherine Woods. This translation reveals the importance of sociocultural tendencies in the translation of literary works. The Senegalese society is the plot of this novel and Kane embedded several sociocultural elements in the source language to convey his message. In this paper, based on Nida’s sociolinguistic theory, we analyze the sociocultural considerations and the stakes in the translation of Kane’s The Ambiguous Adventure. The study shows that sociocultural elements can pose problems to the translator in spite of the undeniable quality of her translation. It is evident that Katherine Woods has to deal with different types of proverbs, idioms and metaphors as used by Kane to show her artistic prowess and knowledge of the vast history of the people. Key Words: Translation, sociocultural, literary, sociolinguistic, theory Résumé L’Aventure ambiguë écrit par Cheikh Hamidou Kane a été traduit en anglais intitulé The Ambiguous Adventure par Katherine Woods. Cette traduction révèle l’importance des tendances socioculturelles dans la traduction des œuvres littéraires. La société sénégalaise sert d’intrigue à ce roman et Kane a intégré plusieurs éléments socioculturels de la langue source pour transmettre son message. Dans cet article basé sur la théorie sociolinguistique de Nida, nous analysons les tendances socioculturelles et ces enjeux de la traduction de L’Aventure ambiguë de Kane. L’étude révèle que les éléments socioculturels peuvent poser des problèmes à la traductrice malgré la qualité indéniable de sa traduction. Il est évident que Katherine Woods doit faire face aux enjeux de différents types de proverbes, d’idiomes et de métaphores utilisés par Kane pour montrer ses prouesses artistiques et sa connaissance de la langue et l’histoire du peuple.